SARS-CoV-2 T-Cell Responses in Allogeneic Hematopoietic Stem Cell Recipients following Two Doses of BNT162b2 mRNA Vaccine - Béatrice Clémenceau; Thierry Guillaume; Marianne Coste-Burel; Pierre Peterlin; Alice Garnier; Amandine Le Bourgeois; Maxime Jullien; Jocelyn Ollier; Audrey Grain; Marie C. Béné; Henri Vié; Patrice Chevallier (Vaccines, 2022)
Background: At variance to humoral responses, cellular immunity after anti-SARS-CoV-2 vaccines has been poorly explored in recipients of allogeneic hematopoietic stem-cell transplantation (Allo-HSCT), especially within the first post-transplant years where immunosuppression is more profound and harmful. Methods: SARS-CoV-2 Spike protein-specific T-cell responses were explored after two doses of BNT162b2 mRNA vaccine in 45 Allo-HSCT recipients with a median time from transplant of less than 2 years by using INF-γ ELISPOT assay and flow-cytometry enumeration of CD4+ and CD8+ T lymphocytes with intracellular cytokine production of IFN-γ and TNF-α. Results: A strong TNF-α+ response from SARS-CoV-2-specific CD4+ T-cells was detected in a majority of humoral responders (89%) as well as in a consistent population of non-humoral responders (40%). Conclusions: T-cells are likely to participate in protection against COVID-19 viral infection, even in the absence of detectable antibody response, especially in the first years post-transplant in Allo-HSCT recipients.